Retrieval of retained fractured intravenous cannula of external jugular vein: a rare report - Chinnamaraju, Nikitha; Sahoo, Samarth; Vamsikrishna, Naga; Ramavath, Krishna; Balchandran, Harikrishna (International Surgery Journal, 2025)
Intravenous cannulation is most common invasive procedure often performed by nursing officers and junior colleagues in the emergency department. Peripheral venous route of upper limb is often preferred over neck venous route. Even though it is a simple routine invasive procedure it can lead to extravascular infiltration, double puncture of vessel walls, thrombophlebitis, hematoma, catheter associated blood stream infections, trauma to surrounding structures like tendon, nerve injuries and air embolism. Fracture of neck intra venous (external jugular vein) cannula in situ is rare and it can cause serious complications if it is neglected. It acts as a retained intravascular foreign body with lethal complications. Hence, the quality of manufacturing of cannula and proper training and technique can prevent potential complications associated with peripheral cannulation. We report a rare case of fractured and slightly migrated intravenous cannula of external jugular vein (EJV) during cannula removal and successfully removed from the EJV under local anesthesia.